Clean graphene surface through high temperature annealing. (November 2015) - Xie, Wenjing; Weng, Lu-Tao; Ng, Kai Mo; Chan, Chak K.; Chan, Chi-Ming
Abstract: The cleanliness of the surface of graphene is important for its proper functioning in devices and sensors. Impurities including residual poly(methyl methacrylate) (PMMA) and hydrocarbon contaminants can alter its electronic and chemical properties. In this study, we used two surface-sensitive techniques, X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS), to monitor the chemical composition of the surface of graphene after washing it with acetone and annealing at high temperatures. The concentration of residual PMMA and hydrocarbon contaminants decreased as the annealing temperature increased. The atomic ratio of sp 3 carbons to sp 2 carbons of a clean graphene surface determined using XPS can be used to estimate the amounts of sp 3 defects in graphene. ToF-SIMS spectra indicate that residual PMMA was removed from the surface of graphene at 400 °C, while hydrocarbon contaminants required a higher temperature of 500 °C to remove. In ToF-SIMS spectra obtained at 500 °C, the characteristic ions for graphene, which are related to cleavage of ring structure, include C x + ( x  = 1, 2, 3…), C x H + and C x H2 + as well as C x − and C x H − . For the first time, we developed a process to produce a very clean graphene surface which was verified by ToF-SIMS and XPS analyses.